Export Scenario Between Bangladesh and China: Opportunities of Bangladesh in RMG Sector - Khan, Ayub Nabi; Ullah, Md. Rashed (European Scientific Journal, ESJ, 2017)
The Ready-made Garment (RMG) industry has already promoted itself as the largest foreign currency earning sector for Bangladesh and occupying the 2nd position in leading exporters of clothing. From a humble beginning in late 70’s RMG sector has emerged itself and did employment about 4.5 million peoples. China is the largest clothing exporter and represents the lion’s share of the world market. In spite of being the second largest exporter, Bangladesh is far behind from China in any category of this sector including export earnings and a number of markets. Whereas China occupies one-third of global market share, Bangladesh has only 6 percent share in clothing export in the world but acts as a lifeline in her economy having 82 percent contribution of export earnings. Bangladesh could be more successful in this sector if it utilizes the available opportunities. For this, Bangladesh should try to grab the opportunities impeding in front because of backwardness of China in clothing export originating recently due to the transformation of the economy to high technology production and higher labor cost in garments. Hence it is important for policy makers to find out the facts and figure in exports of Bangladesh RMG to China. This paper will exhibit the comparativeness of Bangladesh vis-à-vis China in Ready-made Garment sector. Statistical analysis and secondary data sources have been used to make a broad discussion for this study. Bangladesh has the potentialities to be the next China if it can perform well according to the demand and challenges.